2003
DOI: 10.1007/s00244-002-0134-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper on Wild and Tolerant Strains of the Lichen Photobiont Trebouxia erici (Chlorophyta) and Possible Tolerance Mechanisms

Abstract: The influence of copper was assessed on wild and tolerant strains of the lichen photobiont Trebouxia erici and shown to have multiple toxic effects. Addition of 4 mM copper chloride into Trebouxia media reduced growth rates of the wild type to less than 1% of control levels. It also injured cell membranes, inhibited dehydrogenase activity, altered pigment composition, and reduced activity of photosystem II. Membrane damage was assessed through measuring electrical conductivity and potassium content, dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Treated and control thalli of X. parietina showed similar PhQ values among each other (Fig. 4), being in turn comparable to those measured in the epiphytic fruticose lichen Ramalina lacera growing in non-polluted or slightly HM-polluted areas (Garty et al, 2001) and in the aposymbiotically grown photobiont alga Trebouxia erici, exposed to low Cu concentrations (Bačkor et al, 2003). Thus, mechanisms other than substitution of Mg have to be envisaged to explain the considerable loss of Chl noticed in X. parietina thalli exposed to Cd.…”
Section: Intracellular CD Distribution and Effectssupporting
confidence: 78%
See 1 more Smart Citation
“…Treated and control thalli of X. parietina showed similar PhQ values among each other (Fig. 4), being in turn comparable to those measured in the epiphytic fruticose lichen Ramalina lacera growing in non-polluted or slightly HM-polluted areas (Garty et al, 2001) and in the aposymbiotically grown photobiont alga Trebouxia erici, exposed to low Cu concentrations (Bačkor et al, 2003). Thus, mechanisms other than substitution of Mg have to be envisaged to explain the considerable loss of Chl noticed in X. parietina thalli exposed to Cd.…”
Section: Intracellular CD Distribution and Effectssupporting
confidence: 78%
“…Studies on HM toxicity towards lichens mainly concern copper (Cu), zinc (Zn), lead (Pb), manganese (Mn), and chromium (Cr) (Bačkor et al, 2003;Branquinho, 2001;Chettri et al, 1998;Garty, 2000a,b;Hauck et al, 2003;Sanità di Toppi et al, 2004). By contrast, a substantial lack of information as regards the impact of Cd on lichen structure and functions has to be emphasized.…”
Section: Introductionmentioning
confidence: 98%
“…Superoxide dismutase (SOD) activity was measured spectrophotometrically as described by Beyer and Fridovich (1987). In this assay, 1 U of SOD is defined as the amount required to inhibit the photoreduction of nitroblue tetrazolium by 10% (Bačkor et al 2003). Viability of algal cells was assessed via the oxidation of triphenyl-tetrazolium chloride according to Bačkor and Fahselt (2005).…”
Section: Other Methodsmentioning
confidence: 99%
“…Electrical conductivity is considered to indicate injury to cell membranes and has been previously used for the assessment of electrolyte leakage in lichen. [17,18] [21][22][23] Photosynthetic efficiency data in our study has shown that thallus of P. furfuracea can tolerate concentrations of H 2 O 2 at an approximate range of 6-52 µM (see Table 1). de Pinto et al [24] showed that only simultaneous increase of H 2 O 2 in tobacco cells induced cell death that had typical cytological and biochemical features of DNA fragmentation.…”
Section: Discussionmentioning
confidence: 67%